The Implementation of Freewriting Technique in Improving Student's Writing Skill - Caroline S, Ivana; Sriati Usman; Muhammad Arid; Jamiluddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to prove whether or not the implementation of the Freewriting technique is effective in improving students’ writing skills of the eighth-grade students of SMP Negeri 9 Palu. This research used a quasi-experimental design. The Population of this research was class VIII students of SMP Negeri 9 Palu. The researcher used purposive sampling technique and chose two groups: VIII B and VIII D (experimental and control). The instrument used for collecting data was tests (pre-test and post-test). The results of the research show that there was a significance difference in the improve in students writing being taught through free writing technique. Data analysis shows that the t-counted value 10.380 is greater than the t-table value 1.683 by applying a significance level of 0.05 with degrees of freedom (df) = 45. It means that the t-counted is higher than the t-table. It can be interpreted that the hypothesis was accepted. Therefore, the implementation of Freewriting techniques in improving students' writing skills is accepted. The implication of this finding to the teaching practice is that teachers need to apply the freewriting in the learning strategies to make teaching better.